Caracterização da fabricação e uso de compósitos poliméricos contendo fibras naturais com ênfase no polipropileno/sisal a partir da análise de documentos de patentes - Scopel, Felipe (2012)
Natural fibers have became important as substitute for synthetic fiber reinforcement and filling in polymer composites, looking for better properties, lower cost and appeal of sustainability. To do so, there are challenges and limitations to be overcome, such as the compatibility of fiber/matrix, the processing temperature, the moisture absorption and so on. The global auto industry, including Brazil, has led the use of composites containing natural fibers in commercial products and also serves as reference to other economic areas. In Brazil, the fomentation agencies have supported projects in natural fibers and their application in composites, with a significant amount of academic research groups working in this area. The aim of this study was to analyze the situation and trends in the manufacturing and use of materials containing natural fibers through patent analysis, with emphasis on sisal, and also to simulate a sisal/polypropylene composite in home appliance part. Materials, processes, practices and actors involved in these composites were mapped, based on indicators made from patent documents. The analysis of patent documents associated with natural fibers and their use in polymer composites, in the period of 1960 to 2009, demonstrated the growing importance of this subject in the world and particularly in Brazil. Among other results, it was found that Brazil holds the 16th position in patenting associated with natural fibers in general and the 12th place in patenting on the sisal fiber, despite being the world's largest producer of sisal and one of the largest producers of natural fibers in general. Companies and individuals assignees have the largest number of patent documents, when compared to universities and institutes. It was possible to make recommendations for the development of a sisal/polypropylene part through exploratory structural simulation. It was also needed to generate new data to enable simulation of the injection process.